Method to generate high-accuracy high-resolution large-scale crop type maps through integrating agricultural statistics and Moderate Resolution Imaging Spectroradiometer (MODIS) images, with application to China - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The method was tested in Heilongjiang Province, China and generated high-quality crop fraction maps. It can be extended to other crop types and other coarse resolution images.